2012
DOI: 10.1016/j.stem.2011.12.018
|View full text |Cite
|
Sign up to set email alerts
|

A Mammary Stem Cell Population Identified and Characterized in Late Embryogenesis Reveals Similarities to Human Breast Cancer

Abstract: Summary Gene expression signatures relating mammary stem cell populations to breast cancers have focused on adult tissue. Here, we identify, isolate and characterize the fetal mammary stem cell (fMaSC) state since the invasive and proliferative processes of mammogenesis resemble phases of cancer progression. fMaSC frequency peaks late in embryogenesis, enabling more extensive stem cell purification than achieved with adult tissue. fMaSCs are self-renewing, multipotent, and co-express multiple mammary lineage m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
275
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(308 citation statements)
references
References 69 publications
32
275
1
Order By: Relevance
“…Several lines of evidence indicate that mammary glands have evolved from sweat glands (Jenness, 1974;Long, 1969;Oftedal, 2002). We found that sweat gland stem cells share many features with mammary stem cells Spike et al, 2012;Stingl et al, 2006). Similar to mammary stem cells, sweat gland stem cells predominantly reside among myoepithelial cells and are capable of generating exocrine gland-like hollow spheres in vitro.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several lines of evidence indicate that mammary glands have evolved from sweat glands (Jenness, 1974;Long, 1969;Oftedal, 2002). We found that sweat gland stem cells share many features with mammary stem cells Spike et al, 2012;Stingl et al, 2006). Similar to mammary stem cells, sweat gland stem cells predominantly reside among myoepithelial cells and are capable of generating exocrine gland-like hollow spheres in vitro.…”
Section: Discussionmentioning
confidence: 81%
“…Suspension sphere cultures were performed according to Spike et al (2012) with slight modification. Freshly sorted cells were plated on ultralow-adherence plates (Corning, Corning, NY) at 1000 cells/cm 2 in sphere culture medium (Complete MammoCult Human Medium containing 0.5 μg/ml hydrocortisone 21-hemisuccinate (Sigma), 10 ng/ml recombinant human epidermal growth factor (PeproTech, Rocky Hill, NJ), 10 ng/ml recombinant human basic fibroblast growth factor (Stem Cell Technologies), 4 μg/ml heparin (Stem Cell Technologies), and 100 μg/ml penicillin/streptomycin (Gibco)) with or without 2% Matrigel (growth factor-reduced; BD Biosciences).…”
Section: In Vitro Sphere Culturesmentioning
confidence: 99%
“…The demonstration that the mammary gland contains different types of long-lived stem cells has profound implications for our understanding of mammary gland physiology and will be instrumental in unraveling the cells at the origin of breast cancers [116]. The invasive and proliferative processes of mammogenesis in the fetal mammary stem cell state resemble phases of cancer progression [117].…”
Section: Estrogen Signaling In Breast Cancer Stem Cellsmentioning
confidence: 99%
“…Recent studies of the developing mouse mammary gland have revealed that co-expression of CK14 and CK18 occurs in mammary stem cells during embryogenesis, but not subsequently in the adult gland (30,31); such cells can be detected, however, in mouse mammary tumors (32). In the adult human breast, progenitor and stem cell-enriched subpopulations appear to contain cells that express bi-lineage cytokeratins (7,33).…”
Section: Bi-lineage Cells Possess Increased Colony Formation Capacitymentioning
confidence: 99%